Development of a system to integrate safety, productivity, and quality metrics for improved communication and solutions. (September 2020) - Schwerha, D.; Casey, A.; Loree, N.
Highlights: Development of a training program to integrate ergonomics and safety with process improvement. Training program is freely available online. Evaluations indicated that the program improved communication and workplace interventions. Program was evaluated in manufacturing but is applicable to all industries. Training tools can be implemented alone, together, or as part of a Lean/Six Sigma process. Abstract: The implementation of ergonomics in manufacturing to reduce injuries and improve efficiencies requires communication between safety, quality and production professionals. While many ergonomic assessment tools provide indications of risk and suggestions for improvement, few have linked quality and production. Today Lean and Six Sigma are common continuous improvement methods that are utilized in various industries. This article describes a newly developed system that incorporates safety and ergonomics with continuous improvement for better solutions. It incorporates a training program that includes four key tools that can be used alone, together, or within a Lean/Six Sigma structure. Although evaluated at manufacturing sites, this program has the potential to be applicable to other industries, such as healthcare and construction.